Atg11-mediated activation of Atg1 kinase in fission yeast. Issue 2 (1st February 2021) - Pan, Zhao-Qian; Du, Li-Lin
ABSTRACT: The protein kinase Atg1 is a key player in macroautophagy/autophagy, but how its activity is regulated in various organisms is inadequately understood. Our recent study showed that in the fission yeast Schizosaccharomyces pombe, Atg1 kinase activity depends on Atg11, but not Atg13, Atg17, or Atg101. Notably, a 62 amino acid region of S. pombe Atg11 is sufficient for activating Atg1. This region is composed of two parts: an Atg1-binding domain and a homodimerization domain. Atg11 uses this region to dimerize Atg1. Dimerized Atg1 is activated through cis-autophosphorylation.